2006
DOI: 10.1111/j.1475-6773.2006.00548.x
|View full text |Cite
|
Sign up to set email alerts
|

A Cost Analysis of the Iowa Medicaid Primary Care Case Management Program

Abstract: Objective. To determine the cost savings attributable to the implementation and expansion of a primary care case management (PCCM) program on Medicaid costs per member in Iowa from 1989 to 1997. Data Sources. Medicaid administrative data from Iowa aggregated at the county level. Study Design. Longitudinal analysis of costs per member per month, analyzed by category of medical expense using weighted least squares. We compared the actual costs with the expected costs (in the absence of the PCCM program) to estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…This study and the evaluation of the Geisinger PCMH suggest that primary care interventions may require long periods of time to demonstrate financial savings [ 109 , 158 ]. An eight-year study assessing the impact of a primary care case management (PCCM) program in Iowa's Medicaid program did demonstrate reductions in costs due to shifting expenses from the hospital to outpatient setting [ 160 ]. These savings increased over time, reinforcing what other studies suggest: these desired significant cost savings may take time to achieve [ 160 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study and the evaluation of the Geisinger PCMH suggest that primary care interventions may require long periods of time to demonstrate financial savings [ 109 , 158 ]. An eight-year study assessing the impact of a primary care case management (PCCM) program in Iowa's Medicaid program did demonstrate reductions in costs due to shifting expenses from the hospital to outpatient setting [ 160 ]. These savings increased over time, reinforcing what other studies suggest: these desired significant cost savings may take time to achieve [ 160 ].…”
Section: Methodsmentioning
confidence: 99%
“…An eight-year study assessing the impact of a primary care case management (PCCM) program in Iowa's Medicaid program did demonstrate reductions in costs due to shifting expenses from the hospital to outpatient setting [ 160 ]. These savings increased over time, reinforcing what other studies suggest: these desired significant cost savings may take time to achieve [ 160 ]. Chernew et al [ 161 ] explored how PCP/specialist supply influences cost, and the findings indicated that increasing the PCP supply may accrue a short-term advantage but does not address long-term problems.…”
Section: Methodsmentioning
confidence: 99%
“…The Expanded Team consists of a variety of specialty resources. Similar teams have been associated with improvements in efficiency, mortality, hospitalization, access, and coordination [2][3][4][5][6][7][8]. Figure 1 illustrates the relationship infrastructure of PACT team members.…”
mentioning
confidence: 99%
“…Use of the PCCM program was associated with an increase in pharmaceutical expenses but a decrease in hospital and physician expenses. 6 Changing payment methods under insurance plans could also reward accountable care organizations for stewardship of resources. Accountable care organizations are integrated delivery systems, hospital-physician organizations, large physician group practices, networks of primary care practices, or other organizational arrangements large enough to ensure coordination of a comprehensive array of services.…”
mentioning
confidence: 99%